EVALUATION OF PHYTOCHEMICAL AND BIOACTIVE SCREENING OF BLEPHARIS MOLLUGINIFOLIA FLOWER EXTRACTS - S. DEEPIKA; S.V.RAJAGOPAL (International Journal of Pharma and Bio Sciences, 2014)
The present study was aimed to evaluate the Phytochemical, antimicrobial and Cytotoxic activities of the different solvents of flower extract of Blepharis molluginifolia. The Phytochemical constituents of the crude flower extract of B.Molluginifolia using standard tests were performed. Occurrence of phytochemicals depends on the solvent efficacy. In the present study the antimicrobial activity of different solvents of flower extract of B.Molluginifolia by using disc diffusion method and minimum inhibitory concentration by 96 well plated broth culturing method; and also the cytotoxicity of the methanolic flower extract by using Trypan blue staining assay were done. Phytochemical analyses revealed the presence of tannins, flavonoids, steroids and saponins which are very useful in the treatment of diabetes, allergies and cancer. The crude flower extracts in all solvents show broad spectrum activity against all microorganisms we used. A Zone of inhibition of the Blepharis was tested for gram +ve and gram – ve microorganisms and also the four fungal strains. The methanolic flower extract of the Blepharis had the highest activity towards penicilium notatum (33mm), against salmonella typhi (25mm) which causes typhoid fever And against Bacillus subtlis (21mm) for 4000µg/disc concentration. The MIC values of flower extract of B.Molluginifolia (125µg/ml) against all microorganisms’ shows nil growth in the tubes. The methanol extract of the B.Molluginifolia shows 46.8 % inhibition (500 µg/ml). The antimicrobial activity could be confirmed in most species used in traditional medicine in south India most probably by tribes in the nallamala forest region. Nevertheless, traditional knowledge might provide some leads to elucidate potential candidates for future development of ethno botanical antibiotics.